Aberrant Splicing of tau Pre-mRNA Caused by Intronic Mutations Associated with the Inherited Dementia Frontotemporal Dementia with Parkinsonism Linked to Chromosome 17 - Jiang, Zhihong (American Society for Microbiology, 2000)
Frontotemporal dementia accounts for a significant fraction of dementia cases. Frontotemporal dementia with parkinsonism linked to chromosome 17 is associated with either exonic or intronic mutations in the tau gene. This highlights the involvement of aberrant pre-mRNA splicing in the pathogenesis of neurodegenerative disorders. Little is known about the molecular mechanisms of the splicing defects underlying these diseases. To establish a model system for studying the role of pre-mRNA splicing in neurodegenerative diseases, we have constructed a tau minigene that reproduces tau alternative splicing in both cultured cells and in vitro biochemical assays. We demonstrate that mutations in a nonconserved intronic region of the human tau gene lead to increased splicing between exon 10 and exon 11. Systematic biochemical analyses indicate the importance of U1 snRNP and, to a lesser extent, U6 snRNP in differentially recognizing wild-type versus intron mutant tau pre-mRNAs. Gel mobility shift assays with purified U1 snRNP and oligonucleotide-directed RNase H cleavage experiments support the idea that the intronic mutations destabilize a stem-loop structure that sequesters the 5′ splice site downstream of exon 10 in tau pre-mRNA, leading to increases in U1 snRNP binding and in splicing between exon 10 and exon 11. Thus, mutations in nonconserved intronic regions that increase rather than decrease alternative splicing can be an important pathogenic mechanism for the development of human diseases.